2020
DOI: 10.1093/rcfs/cfaa011
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency of Environmental and Social Stocks: An Analysis of the Exogenous COVID-19 Market Crash

Abstract: Abstract The COVID-19 pandemic and the subsequent lockdown brought about an exogenous and unparalleled stock market crash. The crisis thus provides a unique opportunity to test theories of environmental and social (ES) policies. This paper shows that stocks with higher ES ratings have significantly higher returns, lower return volatility, and higher operating profit margins during the first quarter of 2020. ES firms with higher advertising expenditures experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
544
9
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 763 publications
(713 citation statements)
references
References 31 publications
40
544
9
18
Order By: Relevance
“…However, in our study, we assessed health status before the emergency declaration, socioeconomic conditions, and changes in conditions before and after the declaration. Moreover, job loss resulting from the COVID-19 pandemic is exogenous; thus, the present study has found that job loss leads to poor HRQOL (Albuquerque et al 2020 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, in our study, we assessed health status before the emergency declaration, socioeconomic conditions, and changes in conditions before and after the declaration. Moreover, job loss resulting from the COVID-19 pandemic is exogenous; thus, the present study has found that job loss leads to poor HRQOL (Albuquerque et al 2020 ).…”
Section: Discussionmentioning
confidence: 65%
“…Our study has several limitations. First, we could not examine the QOL utility scores due to a lack of baseline information; however, job loss resulting from the COVID-19 pandemic is exogenous, and studies have found that job loss leads to poor HRQOL (Albuquerque et al 2020 ). Second, some of our study results might not be applicable to other countries; the influence of universal financial support on HRQOL might be different depending on the amount.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another rapidly growing literature explores the distinctive effects of the coronavirus pandemic on the cross-sectional structure of firm-level equity returns. Examples include Albuquerque et al (2020), Alfaro et al (2020), Davis, Hansen and Seminario (2020), Ding et al (2020), Hassan et al (2020), Pagano et al (2020), Papanikolaou and Schmidt (2020), and Ramelli and Wagner (2020). 5 6 February 2020.…”
Section: A Sources Of Data For National Outcomesmentioning
confidence: 99%
“… 4 Other studies that examine the various effects of COVID-19 include Albuquerque et al (2020) , and Cheng (2020) . …”
mentioning
confidence: 99%